As vogais médias altas átonas finais em sândi vocálico externo em duas variedades do português do Nordeste brasileiro - Santos, João Paulo Moraes Lima dos (2013)
This study presents an examination of close-mid vowels /e/ and /o/ in unstressed final position in two poorly investigated varieties of Brazilian Portuguese, both from the northeastern area of Brazil. The examination takes into consideration three cases of external vocalic sandhi: degemination, elision and diphthongization. The theoretical frameworks used to support the analysis proposed here are (i) the feature geometry (CLEMENTS; HUME, 1995), (ii) the autosegmental approach to syllable structure, and (iii) the metrical phonology (LIBERMAN; PRINCE, 1977). The material used for the analysis come from two well-stablished corpus of Brazilian Portuguese: the NURC-Recife corpus, which contains interviews with urban, university educated speakers from the state of Pernambuco, and the PRELIN/UFAL corpus, which contains interviews with rural uneducated speakers from the state of Alagoas. The results show that, in both varieties, the close-mid vowels under examination are always pronounced as high vowels in unstressed final position. Besides, it is observed that when the context permits the occurrence of elision or diphthongization, the close-mid vowels involved in these processes are preferably converted into glides, producing, with the following vowel, a rising diphthong. We argue that the final unstressed vowels are elided in the environment of vowels with the same constriction features. This can be particularly observed when the stress and the rhythm patterns of the utterance are taken into consideration. We therefore propose that the context of degemination, as proposed by the literature, should be reconsidered.